Privatization and investment: Crowding-out effects vs financial diversification - Guillaume Girmens; Michel Guillard (Fondazione Eni Enrico Mattei (FEEM), 2002)
In this paper, we study the effect of share issue privatization (SIP) on private investment and financial market under incomplete risk diversification. Risk neutrality and imperfect intertemporal substitutability make investment decreasing in privatization (crowding-out effect). Vice-versa with risk aversion and perfect intertemporal substitutability (diversification effect). Finally, with risk aversion and imperfect intertemporal substitutability, crowding-out effects are more than compensated by diversification effects if and only if risk aversion is sufficiently high (relatively, i.e. compared to the inverse of the elasticity of intertemporal substitution). We establish these results in the most favorable case for the dominance of the crowding-out effect, when the revenues of privatization are devoted to present public consumption.
Keywords: D81; L33; 330; Crowding-out effect; non-expected preferences; privatization; risk-sharing; Privatisierung; Börsengang; Investition; Verdrängungseffekt; Risikopräferenz; Substitutionselastizität; Zeitpräferenz; Theorie